Feasibility Study of Dimoro Animal Market in Blitar City - Atmaja, Muhammad Antar Ariiq; Sterzer , Sebastian; Azizah, Siti; Fitron, Zia Ul Rahman (CV. Komunitas Dunia Peternakan, 2024)
The purpose of this study was to 1. Describe the profile of Dimoro Animal Market, Blitar City, and 2. Analyze the feasibility of the Dimoro Animal Market in Blitar City in August-September 2023. This study uses descriptive and qualitative data analysis. The results of the feasibility analysis of the Dimoro Animal Market show that the Dimoro Animal Market has aspects such as market governance aspects, animal health aspects, market technical aspects, buying and selling transaction aspects, animal welfare aspects, and human health aspects. Dimoro Animal Market Blitar City provides facilities such as livestock weighing, livestock climbing aids, livestock health checks, disinfectant/sanitation spraying, prayer rooms, public toilets, slaughterhouses, and livestock mooring places. It can be concluded that the Dimoro Animal Market in Blitar City is not feasible and needs to be developed and improved standards for the Dimoro Animal Market in Blitar City.